MEDIASI KEPUASAN KERJA ANTARA PENGEMBANGAN KARIR DAN KINERJA PERAWAT RUMAH SAKIT UMUM DAERAH ABDUL WAHAB SJAHRANIE SAMARINDA - Edi Sukamto; Rasmun Rasmun; Sutrisno Sutrisno (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2020)
Achievement of optimal performance can be done if nurses have career development and competence, besides that nurse satisfaction is also a determining factor in Nurse performance. The purpose of this study was to determine the effect of career development and competence on job satisfaction and performance. The population in this study was the Staff Nurses. The sampling technique is Saturated Sampling (Sensus). The sample in this study were all staff nurses who worked in the inpatient ward of the AWS Samarinda regional general hospital, totaling 201 staff nurses. This research was analyzed using the SmartPLS program. The results of this study indicate that career development has a positive and significant effect on job satisfaction, competence has a positive and not significant effect on job satisfaction, career development has a positive and not significant effect on nurse performance, competence has a positive and significant effect on performance, job satisfaction has a positive and significant effect on Nurses performance, job satisfaction has mediates between career development and performance on Nurses AWS Samarinda regional general hospital. Keywords: Career Development, Competence, Satisfaction, Nurse Performance